Bounds of Zagreb type indices of strong product of four operations on connected graphs - Baby, Shakila; Shafiq, Muhammad Kashif; Siddiqui, Hafiz Muhammad Afzal (Utilitas Mathematica, 2022)
The first step in the analysis of a structure is to generate its configuration. The use of graph products is one of the means, available for this purpose. Chemical application of graph theory predicts different properties like physico-chemical properties, thermodynamics properties, chemical activity, biological activity, etc. These properties can be characterized by certain graph invariants known as topological indices. These indices play a vital role in QSAR/QSPR studies. In this paper, the lower and upper bounds of Zagreb indices, multiple Zagreb indices and F-index for strong product of F-sum on connected graphs are determined. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.